Enhance Behavior in Preserving Mangrove Forest Pantai Cermin District, Serdang Bedagai Regency - Muhammad Toyib Daulay; Annisa Ilmi Faried; Edi Saputra Matondang (Rowter Journal, 2023)
Mangrove is a type of ecosystem typical of those found along the coast that are affected by tides. Mangroves grow on sheltered beaches or flat beaches, usually along the wind-sheltered side of the island or behind coral reefs off protected shores. The community around mangroves in Pari City Village, Pantai Cermin District, Serdang Bedagai Regency has long been utilizing the various mangrove potentials around the community. In general, people use mangroves for their economic potential income. The utilization is generally in the form of looking for firewood from mangrove forests, ponds, food from mangroves and tourism. Mangroves are also the main ecosystem supporting important life in coastal and marine areas. In addition to having an ecological function as a nutrient provider for aquatic biota, spawning and caring places for various kinds of biota, coastal abrasion resistance, the risk of typhoons and tsunamis, waste absorbers, and preventing seawater interusion. Due to the high damage to the mangrove area in the Pari City Village area, Pantai Cermin District, Serdang Bedagai Regency, it can cause several problems, including reducing the productivity of natural resource ecosystems biologically, increasing pollution and the most disadvantaged are the people around the coastal suburbs who have a source of income from fishermen Where their livelihoods are declining due to fish caught already scarce.